Study of the dinuclear system for 296119 superheavy compound nucleus in fusion reactions. (April 2021) - Mohammadi, J.; Ghodsi, O. N.
Abstract: This investigation aims to find an appropriate dinuclear system for the formation of 119 superheavy compound nucleus. By studying the driving potential and measuring the capture cross section of the reactions, the evolution of the dinuclear system can be understood. In this study, we obtained capture, fusion, and evaporation residue cross sections and survival probability at energies near the Coulomb barrier for four reactions, namely Sc + Cf, Ca + Es, K + Fm, and Ar + Md. Our calculations show that the reaction Ar + Md is a suitable choice for the formation of an element with 119 protons among the studied reactions from a theoretical viewpoint.